Efficacy and safety of 4‐hydroxy 2‐methyl‐N‐(5‐methyl‐2‐thiazolyl)‐2H‐1, 2‐benzothiazin‐3‐carboxamide 1,1‐dioxide, a fast‐acting meloxicam formulation, on moderate‐to‐severe pain following abdominal surgery: A phase III randomized controlled trial - Xiaohua Liu; Yanhua Zhao; Mengchang Yang; Jinghua Ren; Wen Ouyang; Saiying Wang; Yufei Shen; Yuanli Gao; Ling Zhao; Zhong Qin; Jun Cao; Jiangyan Xia; et al. (Clinical and Translational Science)
Abstract 4‐hydroxy 2‐methyl‐N‐(5‐methyl‐2‐thiazolyl)‐2H‐1, 2‐benzothiazin‐3‐carboxamide 1,1‐dioxide (QP001), a novel long‐lasting meloxicam formulation, may provide adequate postoperative pain relief with a good safety profile. This study aimed to evaluate the efficacy and safety of QP001 for moderate‐to‐severe pain following abdominal surgery. This multicenter, randomized, double‐blind, placebo‐controlled phase III trial recruited patients undergoing abdominal surgery at 23 centers between October 30, 2022, and July 10, 2023. Patients were randomized to a QP001 or placebo group in a 2:1 ratio. Postoperative pain intensity was evaluated using the Numerical Rating Scale. The primary efficacy outcome was the area under curve (AUC) of pain intensity‐time 0–24 h after awakening from anesthesia (AUC0–24). Adverse events and drug reactions were recorded to evaluate safety. A total of 258 patients underwent randomization, and 255 patients received at least one trial drug, including 170 in the QP001 group and 85 in the placebo group. Among these patients, 250 completed the study. The AUC0–24 was significantly lower in the QP001 group than in the placebo group (50.5 vs. 85.19, difference of 34.69 [40.7%], p < 0.0001). This was accompanied by a decrease in morphine use and an increase in patient satisfaction. Moreover, the overall adverse events or adverse drug reaction rates were similar between the QP001 and placebo groups. Among patients undergoing abdominal surgery, postoperative pain was significantly lower in the QP001 group than in the placebo group. QP001 has a great analgesic effect of up to 24 h and satisfactory safety in patients with moderate‐to‐severe abdominal pain.